(NgEOLOGI^ESKAQ KARTA sREDNEJ aZII (B:s (NlIST k(B-44-(Na `GO(B-(NwOSTO^NAQ ^ETWERTX (B((NhAN(B-(NtENGRI(B) : (NmAS[TAB (B1:500 000 /s - (N{ULXC(B, (Ns(B.(Nss ((NlENINGRADs (NmOSKWA (B:s (NgOSTOPTEHIZDAT(B,s, 1940)
(NzAKL(B. : (NS(B. 265-283s
(NpODSTR(B. (NPRIME^(B.s
(NlIT(B. : (NS(B. 284-289( (NNA RUSS(B. (NI IN(B. (NQZ(B.)s
Keywords: (NgEOLOGIQ (B- (NsREDNQQ aZIQs